PENERAPAN SISTEM KESELAMATAN DAN KESEHATAN KERJA (K3) DALAM MENINGKATKAN KINERJA KARYAWAN PT PASIFIK PRIMA PERKASA CILEUNGSI BOGOR - Tanzala Azzahra; Reni Hindriari (Journal of Research and Publication Innovation, 2025)
Human Resources (HR) is a crucial element in the continuity and success of an organization or company. HR plays a strategic role in executing various organizational functions, such as formulating strategies, innovations, and achieving goals. To ensure the company's success, HR quality must be enhanced through performance improvement, which can be achieved by implementing an effective Occupational Health and Safety (OHS) system. This study aims to analyze the implementation of the OHS system and its impact on improving employee performance at PT Pasifik Prima Perkasa Cileungsi Bogor. The research used is descriptive with a qualitative approach, with data collection methods through observation, interviews, and documentation. The obtained data were analyzed using SWOT analysis and data validity testing through triangulation techniques. The results indicate that the implementation of the OHS system at PT Pasifik Prima Perkasa plays a significant role in improving employee performance and minimizing the risk of workplace accidents. The implementation of the OHS system, which refers to Government Regulation No. 50 of 2012 on Occupational Safety and Health Management Systems (OSHMS), is key to maintaining employee welfare and enhancing company productivity.